Implikasi Tahfiz Alquran Terhadap Akhlak Remaja di Kelurahan Pasar Sibuhuan Kecamatan Barumun Kabupaten Padang Lawas - Hirayani Siregar (Studi Multidisipliner: Jurnal Kajian Keislaman, 2021)
This study aims to determine the process of implementing the Qur'anic tahfiz in the Sibuhuan Market Village and the implications of the Qur'anic tahfiz for the morals of adolescents in the Sibuhuan Market Village, Barumun District, Padang Lawas Regency. The results of this study indicate that the process of implementing tahfiz Alquran at the Tahfiz Alquran Sibuhuan house has gone quite well, it can be seen from the memorization process, memorization material in each phase, the method used, and the evaluation system that has been well planned. However, in the process of implementing the Qur'anic tahfiz there are several supporting and inhibiting factors. The supporting factors for the implementation of tahfiz Al-Quran are good physical and psychological, full support from the tahfiz house, and giving rewards to students. Meanwhile, the inhibiting factors for implementing the Qur'anic tahfiz are laziness and despair. Furthermore, the implications of the Qur'anic tahfiz for adolescent morals are that there are several morals towards fellow humans including morals towards oneself, morals towards parents, morals towards society, and morals towards peers